Evaluation of population growth of daphnia magna feeding Ulva lactuca - Laheng, Suardi; Herjayanto, Muh.; Putri, Ika Wahyuni (Acta Aquatica: Aquatic Sciences Journal, 2023)
Success in the fish hatchery is influenced by natural feed. One of the natural freshwater feeds that have a high nutritional content and is easy to cultivate is Daphnia magna. The availability of D. magna at any time must be supported by daily feeding. Ulva lactuca macroalgae is one of the ingredients that have the potential to be used as D. magna feed because it has good nutrition and is abundantly available on the coast. This research was conducted for 17 days at the Integrated Laboratory of Madako Tolitoli University. The aim of the study was to determine the population growth of D. magna fed          U. lactuca. D. magna was reared in a 25 x 25 x 30 cm aquarium containing 5 liters of green water and a stocking density of 20 individuals/L. The treatments tried were Treatment A = Without U. lactuca Soak (0 ml/L), Treatment B = U. lactuca Soak (3 ml/L), Treatment C = U. lactuca Soak (5 ml/L). The results showed that the administration of U. lactuca 5 ml/L (804.44 ind/L) had the highest population growth compared to the treatment of 3 ml/L immersion of U. lactuca (597.78 ind/L) and without administration of immersion of U. lactuca (482.22 ind/L). Treatment of U. Lactva 5 ml/L is effective in increasing Growth D. Magna and can be an alternative feed D. Magna whose availability is abundant in the coastal area.Keywords: Daphnia magna; growth; Ulva lactuca